2020
DOI: 10.1108/heswbl-04-2020-0055
|View full text |Cite
|
Sign up to set email alerts
|

Developing WIL curriculum which enhances hospitality students capabilities

Abstract: PurposeTo satisfy multiple stakeholders’ employability goals, higher education providers have introduced Work Integrated Learning (WIL) programs to provide opportunities for students to develop the required skills. Yet despite this increased focus, gaps in graduate capabilities persist. Thus, the paper explores the roles of educators, industry and students in co-creating WIL curriculum which provides transformative learning experiences.Design/methodology/approachA survey was designed using the Professional Cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…6990 higher learning institutions are failing to embed GAs into their curriculum (Halibas et al 2020)- Staunton et al 2021) outline the difficulty of dealing with various higher learning stakeholders, which could be confusing due to varying responses on GAs. According to (Williamson et al 2021), a lack of student consultations on GAs results in graduates' unpreparedness. Furthermore, Wong et al (2022), reciprocate the need for students' involvement in GAs if an 'ideal graduate' is to be shaped.…”
Section: Resultsmentioning
confidence: 99%
“…6990 higher learning institutions are failing to embed GAs into their curriculum (Halibas et al 2020)- Staunton et al 2021) outline the difficulty of dealing with various higher learning stakeholders, which could be confusing due to varying responses on GAs. According to (Williamson et al 2021), a lack of student consultations on GAs results in graduates' unpreparedness. Furthermore, Wong et al (2022), reciprocate the need for students' involvement in GAs if an 'ideal graduate' is to be shaped.…”
Section: Resultsmentioning
confidence: 99%
“…In the sports industry, interpersonal skills are seen as important soft skills for students to get a job because studies have shown interpersonal relationships have a significant impact on the services provided to users (Miller et al, 2022), and leadership skills also were referred as highly relevant because as part of a team, they need to know to lead the work and take decisions (Silva et al, 2019). Williamson et al, (2020) relate interpersonal capabilities relate to an individual's capacity to influence or empathize with others. Furthermore, the study that been conducted by Marneros et al, (2021) found in the hotel industry, which is labor-intensive always stressed communication skills as the most important competency dimension.…”
Section: Skillmentioning
confidence: 99%
“…Chalupa & Chadt (2021) also emphasized that flexibility, professionalism, empathy, and emotional resilience are equally vital attributes. Williamson et al, (2020) underscored the importance of emotional intelligence for hospitality workers who need to be able to empathize with others effectively in addition to committing. According to Lu et al, (2021), critical abilities comprise effective performance at work along with good ethics and integrity.…”
Section: Attitudementioning
confidence: 99%